1997
DOI: 10.1002/elps.1150180807
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the predicted and observed properties of proteins encoded in the genome of Escherichia coli K‐12

Abstract: Mining the emerging abundance of microbial genome sequences for hypotheses is an exciting prospect of "functional genomics". At the forefront of this effort, we compared the predictions of the complete Escherichia coli genomic sequence with the observed gene products by assessing 381 proteins for their mature N-termini, in vivo abundances, isoelectric points, molecular masses, and cellular locations. Two-dimensional gel electrophoresis (2-DE) and Edman sequencing were combined to sequence Coomassie-stained 2-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
266
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 338 publications
(295 citation statements)
references
References 130 publications
29
266
0
Order By: Relevance
“…When the assays were performed using late-stationary-phase cells (overnight cultures), the activity found was about 10-fold higher than that in exponential-phase cells (data not shown). Such high expression is consistent with the high amount of HdeA protein reported under similar conditions (25). At pH 5.5, the expression of hdeAB in exponential phase showed no significant increase compared to that at pH 7.0, even though other authors have found acid induction in exponential-phase cells grown under different conditions (19,43).…”
Section: Vol 190 2008supporting
confidence: 90%
See 1 more Smart Citation
“…When the assays were performed using late-stationary-phase cells (overnight cultures), the activity found was about 10-fold higher than that in exponential-phase cells (data not shown). Such high expression is consistent with the high amount of HdeA protein reported under similar conditions (25). At pH 5.5, the expression of hdeAB in exponential phase showed no significant increase compared to that at pH 7.0, even though other authors have found acid induction in exponential-phase cells grown under different conditions (19,43).…”
Section: Vol 190 2008supporting
confidence: 90%
“…The determined HdeA crystal structure and the model HdeB structure are similar (14,45), in agreement with their genetic and functional similarities. HdeA is one of the most abundant periplasmic proteins in stationary phase (25).…”
mentioning
confidence: 99%
“…We have identi®ed such values from the published literature and from a 2-D electrophoresis survey in our laboratory (Link et al, 1997) for 16 of the proteins in our study (Table 4). Comparison of our predictions to the observed protein abundances suggests that many of our matrices are underspeci®c; many more sites are predicted than are expected from protein abundance levels.…”
Section: Comparison Of Matrix Searches With Actual Binding-site Abundmentioning
confidence: 99%
“…10,12 There are six subgroups of PRDX enzymes (PRDX1-6) in mammals. [12][13][14] These enzymes use redox-active cysteines to reduce peroxides, and are divided into two categories, 1-Cys and 2-Cys, based on the number of cysteinyl residues directly involved in catalysis 3 . The peroxidase reaction is composed of two steps centered around a redox-active cysteine designated 'peroxidatic cysteine'.…”
Section: Introductionmentioning
confidence: 99%